PENGEMBANGAN MEDIA PEMBELAJARAN MATA KULIAH FISIOLOGI TUMBUHAN BERBASIS E-LEARNING DENGAN MENGGUNAKAN SOFTWARE MOODLE - Abd. Muis; Ismail Ismail; Arsah Bahri (Universitas Negeri Makassar, 2017)
This study is aimed to develop Plant Physiology instructional media based on e-learning by using LMS Moodle which is valid. in overcoming the limitations of the time allocation in the classroom, increase student activity and student learning outcomes. This study is R&D, research conducted to determine the initial state of learning Plant Physiology during this early in Biology Department, Mathematics and Natural Science Faculty, Makassar State University and student characteristics. Development is done to plan, product, test, and validate instructutional media. Validity is done by two validators. Test phase consisted of initial test and field test. Initial test consisted of expert evaluation.